Cultural Beliefs of Kejawen as Life Form of the Javanese in Islamic Theology Perspective - Suroyo; Bima (JURNAL PENELITIAN, 2023)
Kejawen is the belief of a multi-ethnic people on the Indonesian island of Java. Kejawen philosophy is based on Javanese thinkers' religious beliefs. This study aims to analyze the cultural beliefs of Kejawen from an Islamic Theology perspective with the objectives of this study are to determine the ritual of Kejawen in daily life from Islamic perspective and the materials used such as flowers and offerings in Kejawen which will be studied in Islamic perspective. This is an ethnographic study with the location of this study being in the Special Region of Yogyakarta and Solo. Documentation and observation are the instruments which are used for this study.  The result found that Kejawen is an example of this fusion, with many Islamic elements. In Kejawen, God is known as Sang Hyang Taya, which is connected to the Islamic idea of Allah. Muslims believe that Allah is the one God and that no other gods exist. From an Islamic theological stance, Kejawen emphasizes the importance of inner spirituality, human experience, and the interconnection of all things in the cosmos. There are many connections between it and Islamic ideas, including as the concept of God and the power of prayer.